Technological Innovation in the Independent Learning-Independent Campus (MBKM) Program at the Information Systems Study Program, Faculty of Computer Science, Subang University - Cahya Ramdan Syah; Franciskus Antonius Alijoyo; Bagus Ali Akbar (SEAN Institute, 2023)
The Merdeka Belajar-Kampus Merdeka (MBKM) Program is a policy launched by the Minister of Education in 2019, aimed at giving students more control over their educational journey. Subang University, especially the Information Systems study program, has participated in this MBKM Program, has played an important role in implementing the vision of this initiative. In the midst of technological developments, innovative approaches and the use of technology are essential in achieving the goals of this program. In its implementation, there are various responses from students or lecturers, and become material for evaluation. This research aims to bring up technological innovations that can be applied to increase the level of effectiveness and efficiency of the educational process, the research method used is descriptive qualitative, the data collection stage is based on data on students who take the MBKM program, the distribution of accompanying lecturers, activities that have been running, and raises several obstacles in the implementation process, then from the results of these findings the authors enter into data groups based on the MBKM program, then describe the proposed technology, information system integration, then compare with the previous system which includes time, cost, human resources involved and implementation procedures.